A functional limit theorem of the type of the law of large numbers for random reliefs - Yurachkovskii, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For a random function dependent on time and on a point of a space with measure, we find an asymptotic expression for the measure of the region in which values of the function do not exceed a given level.